Cuba and the armed conflicts (1956-1989): Local actor or caught between bipolar and patterns of politics (Tzintzun, Revista de Estudios Históricos, 2016)
Since the 16th century, when the geographically small island servedas a military base for the devastation of the Aztec empire by the Spanishconquerors, Cuba has always played a strategic role for the empiresof the world. Although Cuba’s economic performance depended ingeneral on its integration in the economic structures of the prevailingempires, during the last centuries the cosmopolitan elites of Havanaalways had some influence on the imperial officials in Madrid, Washingtonor Moscow.